Diagnostic Accuracy of Ultrasound in Detection of Synovial Hypertrophy in Patients with Osteoarthritis - Sidra Manzoor , Rabia Waseem Butt , Sidra Nadeem , Fazeela Farid , Manal Niazi , Sidra Manzoor , Rabia Waseem Butt , Sidra Nadeem , Fazeela Farid , Manal Niazi (Journal of Rawalpindi Medical College, 2017)
Objective: To determine the diagnostic accuracy of ultrasound in the detection of synovial hypertrophy in patients with osteoarthritis by using MRI as the gold standard. Methods: In this descriptive study, 150 patients with complaint of joint pain and stiffness, were included. Ultrasound was carried out. Subsequently, MRI scan of affected joint was performed. Results: By taking the synovial thickness of more than 2.3mm as discriminatory level for synovial proliferation, the overall sensitivity of ultrasound was 94.23%, and specificity was 87.23%. The positive predictive values of the ultrasound in patients with synovial hypertrophy was 95.14% and negative predictive value was calculated to be 92.67%. The diagnostic accuracy of the test was 89.12%. Conclusion: Duplex Doppler ultrasound can detect synovial hypertrophy with sensitivity of approximately 94.23 %